Improvement of power grid stability and load distribution using diesel excitation controller - Ehsan Ganji; Mehdi Mahdavian (Journal of Mechatronics, Electrical Power and Vehicular Technology, 2022)
One of the requirements for controlling hybrid power systems is designing an appropriate excitation system, flexibility, protection, and coordination of all components to improve system stability. In this paper, various types of equipment simulated in the linear form and non-linear models are connected to the power supply. In the same direction, while presenting a new controller for the diesel generator excitation system and a filter used to purify and attenuate current harmonics is reported on the stability of a grid-independent system. Finally, the variation of the mode for the voltage and power of the system has been confirmed at the time of error and complete system stability. Also, the important indicators in the analysis are obtained in the lowest values, which can be seen from the controlled harmonics of the system of this data. In addition, the variation of the mode for the voltage and power of the system has been confirmed and the important indicators in the analysis are obtained in the lowest values.